Valvular heart disease during pregnancy: a clinical case and a literature review - Bužinskienė, Diana; Domža, Gintautas; Dulko, Justyna; Olšauskaitė, Miglė; Drąsutienė, Gražina; Liekienė, Daina (Acta medica Lituanica, 2019)
Background. As a result of improved diagnostic and reparative techniques, congenital heart diseases are becoming a significant problem for women of childbearing age. Nowadays, more pregnant women in the West are being diagnosed with an acquired heart disease because of the tendency to delay childbearing and increasing age-related risk of developing complications of hypertension, diabetes, obesity and other diseases. According to the Lithuanian Health Information Centre, the incidence of cardiovascular diseases in pregnancy is decreasing in Lithuania, from 1.4% in 2014 to 1% in 2016 (1). Heart diseases can aggravate maternal adaptive capabilities and complications that pose a threat to mother and foetus can occur. Management of such conditions presents a serious therapeutic challenge to multidisciplinary team. The aim of this article is to discuss the course of pregnancy and peculiarities of maternal and foetal care in a woman with hemodynamically significant heart disease. Materials and methods. We present a clinical case of a 30-year-old nuliparous woman who was diagnosed with mitral valve disease with critical stenosis, grade II/III mitral valve insufficiency, moderate-severe pulmonary hypertension, heart failure stage C, and NYHA functional class II. Results and conclusions. Pregnancy in conjunction with heart disease is a complicated condition that requires multidisciplinary prenatal care (consisting of an obstetrician gynaecologist, cardiologist, anaesthesiologist). Low molecular weight heparins should be the first choice medication for antithrombotic prophylaxis. Since pregnancy can aggravate a heart disease, preconception counselling and evaluation of the heart function are recommended.